Tetralogía de Fallot en poni: Caso clínico (2024)
This degree work with an internship modality is carried out at the Foal Care clinic, a comprehensive equine care clinic that seeks to offer solutions for horse breeders and horses. field veterinarians, being the main site of medical care for foals, mares and ponies in the Bogotá savannah.